2011
DOI: 10.1128/aac.01134-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of the Multidrug-Resistant Acinetobacter baumannii Strain MDR-ZJ06 Widely Spread in China

Abstract: We previously reported that the multidrug-resistant (MDR) Acinetobacter baumannii strain MDR-ZJ06, belonging to European clone II, was widely spread in China. In this study, we report the whole-genome sequence of this clinically important strain. A 38.6-kb AbaR-type genomic resistance island (AbaR22) was identified in MDR-ZJ06. AbaR22 has a structure similar to those of the resistance islands found in A. baumannii strains AYE and AB0057, but it contained only a few antibiotic resistance genes. The region of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 35 publications
3
94
0
Order By: Relevance
“…The complete genome sequencing of Acinetobacter spp. showed that, even for isolates sharing the same genetic background that were collected from the same country and the same time period, the locations of bla OXA-23 can be different (10,15). This phenomenon suggests that frequent horizontal transmission of this carbapenemase-encoding gene is possible, which is distinct from the simple clonal spread we previously anticipated (14).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…The complete genome sequencing of Acinetobacter spp. showed that, even for isolates sharing the same genetic background that were collected from the same country and the same time period, the locations of bla OXA-23 can be different (10,15). This phenomenon suggests that frequent horizontal transmission of this carbapenemase-encoding gene is possible, which is distinct from the simple clonal spread we previously anticipated (14).…”
mentioning
confidence: 70%
“…Four main transposons, Tn2006, Tn2007, Tn2008, and Tn2009, were found to be associated with the transfer of bla in A. baumannii (5,(9)(10)(11). Besides sharing a common region (OXA-23-⌬ATPase), all the transposons have ISAba1 upstream from bla OXA-23 except Tn2007, which is correlated with ISAba4 (5, 9-11).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The second model, AbaR4-like, consists of Tn6022 as a backbone transposon and has mainly been identified among isolates from international clone II (11)(12)(13)(14). Complex structures of AbaR4-like islands, such as Tn6167 and AbaR22, have recently been described (15,16). Importantly, the AbaR4-like islands have repeatedly been found to be interrupted by Tn2006 carrying the bla OXA-23-like gene (12)(13)(14)(15).…”
mentioning
confidence: 99%